Newsroom Disruptions and Opportunities in Times of Crisis: Analysing Southern African Media During the COVID-19 Crisis. Issue 2 (3rd April 2022) - Chibuwe, Albert; Munoriyarwa, Allen; Motsaathebe, Gilbert; Chiumbu, Sarah; Lesitaokana, William
ABSTRACT: The COVID-19 pandemic currently ravaging the world has brought massive disruptions to every facet of life. However, a crisis can present revolutionary change and growth opportunities for both individuals and institutions. This study is a cross-country study that examines the disruptions and opportunities that the pandemic has wrought to mainstream news reporting practices. Utilising data from Botswana, South Africa and Zimbabwe, we seek to answer the question: in what ways did the pandemic disrupt news production, and what opportunities to the mainstream media did the pandemic open? To answer this question, we utilise in-depth interviews with practising journalists and draw on the interaction of Schudson's sociological view of news production and Bourdieu's field theory. We note that the pandemic disrupted news sourcing routines in ways that compromised the quality of news production. Paradoxically, amidst this disruption, we notice that media–state relations and trust in mainstream media improved dramatically. This makes us argue that the pandemic represented an opportunity for mainstream media to "reset" their existential purpose, considering how they revitalised their relations and how they reclaimed declining trust in them. We conclude that COVID-19 may have breathed a new lease of life into a declining journalism industry.